Vitamin D Deficiency Linked To Depression (Systematic Review: Meta Synthesis) - Talitha Salsabila; Indranila Kustarini Samsuria; Dwi Retnoningrum; Indah Saraswati (Jurnal Kedokteran Diponegoro)
Background: Depression is a mood disorder that is marked by a persistent feeling of sadness, loss of interest; reduced energy and vitality; feelings of low self-worth or guilt; loss of appetite; disturbed sleep or insomnia; and slowness of thought or action. Vitamin D deficiency has been associated with depression. When the level of Vitamin D and serotonin is low, that leads to depression.